Diagnostic and prognostic markers of oral squamous cell carcinoma- a detailed review - R. Ashwini; Madhu Narayan; K. Rajkumar (Oral Oncology Reports)
Oral Squamous Cell Carcinoma (OSCC) is one of the most common tumours of oral cavity. It has a high mortality and morbidity rate that can be greatly reduced by early diagnosis and intervention. The conventional diagnostic methods like biopsy may not aid in the early diagnosis of the lesion. It is at this point that the tumor markers play an important role. Tumor markers relay information on current status of the lesion and also about the potential metastatic activity of the ongoing cancer. The ideal requirement of tumour marker should be that it must be sensitive and specific and it should not produce false negative and false positive results. Tumour markers should be easily available and it should be able to differentiate between non-neoplastic and neoplastic lesions. The tumour marker should be able to predict the recurrence and it should have a great prognostic value. This review article particularly focuses on various tumour markers pertaining to Oral Squamous Cell Carcinoma. We searched PubMed and Google Scholar for literature about tumour markers associated with OSCC published in English until December 2022 for this review. The pertinent data from the relevant papers were extracted and synthesised into a single review.